Hvorfor er religionssosiologien så klasseblind? - Repstad, Pål (Religionsvidenskabeligt Tidsskrift, 2023)
SUMMARY: After a period with a strong focus on individualization and on other social background factors like gender and ethnicity, social class is back as a central topic. However, in sociology of religion its seems that class is still rarely investigated. This is also the case in the Nordic countries. In this article some examples are presented of how some of the founding fathers in sociology looked at the mutual relationship between social class and religious life. Then follows a discussion about why the increased interest in class analysis to little extent has manifested itself in the sociology of religion. The empirical examples are for the most part Norwegian, but the arguments have probably a broader relevance. RESUME: Etter en periode i sosiologien med sterkt fokus på individualisering og på andre sosiale bakgrunnsfaktorer som kjønn og etnisitet, er sosial klasse tilbake som et sentralt tema. I religionssosiologien ser det imidlertid ut til at temaet klasse fremdeles utforskes sjelden. Det gjelder også i Norden. I denne artikelen presenteres noen eksempler på hvordan noen av de sosiologiske klassikerne så på det gjensidige forholdet mellom sosial klasse og religiøst liv. Så følger en diskusjon om hvorfor den økte interessen for klasseanalyse i sosiologien i liten grad har gjort seg gjeldende i religionssosiologien. De empiriske eksemplene er stort sett norske, men argumentene har trolig bredere relevans.